Strategy To Strengthen Cooperation Between The European Union And The Mediterranean Countries Through The Union For Mediterranean (UfM) - Elistania, Elistania; Nurmeiga, Farandy; Permadi, Agung (Global: Jurnal Politik Internasional, 2019)
The European Union is an example of regional cooperations that represents regional identity. In the midst of the process of integration and expansion of membership, the European Union has an interest in building good relations with non-member countries in the immediate region, including the Mediterranean. The process of establishing cooperation between the European Union and the Mediterranean countries continues to change. The Euro-Mediterranean Partnership (EMP) in 1995 was the place for regional cooperation with most member countries and had a well-structured pillar of cooperation. However, the two entities re-formed a new cooperative platform, The Union for Mediterranean (UfM) in 2008. This study aims to explain why the European Union and Mediterranean countries changed the Euro-Mediterranean Partnership (EMP) into The Union for the Mediterranean (UfM) in 2008. Using the theory building approach in the Alex Warleigh-Lack regionalism concept, the findings in the research resulted in an answer that EMP has negative values that are not in accordance with the development of the issue so that it becomes a reason for the formation of UfM.